Higher-order memory schema and consciousness experience. Issue 3 (18th May 2020) - Brown, Richard; LeDoux, Joseph
ABSTRACT: In the interesting and thought-provoking article Grazziano and colleagues argue for their Attention Schema Theory (AST) of consciousness. They present AST as a unification of Global Workspace Theory (GWT), Illusionism, and the Higher-Order Thought (HOT) theory. We argue it is a mistake to equate 'subjective experience, ' ad related terms, with dualism. They simply denote experience . Also, as presented, AST does not accurately capture the essence of HOT for two reasons. HOT is presented as a version of strong illusionism, which it isn't, and HOT requires that one be aware of one's mental life, and postulates that his consists in a re-representation of what is occurring at at the lower-order levels. However, the authors deny that AST involves re-representing visual stimuli. We close by proposing an alternative unification: GWT and AST provide crucial accounts of how lower-order states are assembled and maintained, but higher-order theory provides the account of subjective experience.